Flytsoner Studiar i flow og rap-lyrikk - Markussen, Bjarne (Spartacus Forlag AS / Scandinavian Academic Press, 2022)
Rap as a vocal expression has become everyone's property. From having been one of four elements in the early hip-hop underground, rap has found its way to all the nooks and crannies of the world. Rap is done in all kinds of languages in all kinds of contexts - from marginal micro-genres to the broadest mainstream. Rap lyrics are the most widespread form of lyrics in the 21st century. It is an oral poem, characterized by a peculiar form of performance. In the flow, the linguistic and musical rhythm play together in an intricate way. Rap lyrics are an arena for contemporary commentary and self-assertion, but also for reflection, community, language play and humour. This book is about rap as an aesthetic expression. It deals with rhythms and melodies, rhymes and punchlines, whimsical chains of association and ambitious concept albums. Read about Elling Borgersrud, Runar Gudnason, Lars Vaular, Linni, MC Einar, SuparDejen, Deichkind, Jaa9, Sivas, Geeza G, Vigsø, Kae Tempest, George Watsky and more.